LITERARY REVIEW ON SHANKHA - Dr swathi K.S, Dr priya K.pillai, Dr Shyamveer Gurjar, Dr Mayukh Sharma (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2019)
Ayurveda comprise of drugs derived from herbs,minerals, metals and animals. But they can’t be taken as it is, hence need to be converted into such form which will be therapeutically fit for use. Rasashastra is the most important and popular branch of Ayurveda which was developed in the medieval period. Bhasma are the unique dosages form of Ras Shastra, prepared after proper bhavana with particular herbs with particular metals and minerals and later they are subjected to puta in a particular manner and due to its fineness and nano particle size it turn into most assimilatory, harmless and therapeutically effectual form Key words-Rasashastra ,shankha,bhasma